Harry Potter que(e)r: Eine Filmsaga im Spannungsfeld von Queer Reading, Slash-Fandom und Fantasyfilmgenre - Dr. Vera Cuntz-Leng (transcript, 2015)
Harry Potter's enchanted world is more than just magic and colorful. The double-perspective of academia and online fan culture shows that it is also queer.